Fair Trade in a tourist product - Bożydaj-Jankowska, Iwona (Fair Trade w produkcie turystycznym, 2019)
The main purpose of this theoretical and empirical article is to present the concept of Fair Trade and refer it to a tourist product, as well as to characterize the tourism market operating within the Fair Trade certification system. The subject of the analysis is the Fair Trade concept, its goals and principles, and its certification system in the context of a tourist product. The author of the article attempts to answer the question whether the concept of Fair Trade realized in the tourism sector can be helpful in achieving the goals of sustainable tourism, and what is the potential of Fair Trade Tourism in becoming the dominant idea/ concept and mainstream in the development of sustainable tourism. The article contains an analysis of selected aspects of Fair Trade Tourism based on annual reports of Fair Trade Tourism South Africa
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 12, s. 167-178